The Association of International Normalized Ratio with Postoperative Complications in Revision Total Knee Arthroplasty - Churchill, Jessica L.; Samuel, Linsen T.; Karnuta, J. M.; Acuña, Alexander J.; Kamath, Atul F. (The Journal of Knee Surgery, 2019)
The purpose of this study was to examine the relationship between elevated preoperative international normalized ratio (INR) and (1) mortality, (2) postoperative bleeding, and (3) other postoperative complications in a national cohort of patients who underwent revision total knee arthroplasty (rTKA). The American College of Surgeons National Surgical Quality Improvement Program was queried for rTKA procedures conducted between 2006 and 2017. Cohorts were based on INR ranges: <1, 1 < INR ≤ 1.25, 1.25 < INR ≤ 1.5, and >1.5. Univariate/multivariate statistics were calculated to analyze associations between INR value and designated covariates. These statistics were additionally applied to optimal cutoff values of INR calculated using a receiver operating characteristics curve. The final cohort consisted of 1,676 patients. Progressively higher INR values were associated with an increased risk of mortality within 30 days (p < 0.006), bleeding requiring transfusion (p < 0.001), sepsis (p < 0.001), return to the operating room (Odds Ratio [OR], p = 0.011), reintubation (p < 0.001), pneumonia (p < 0.001), failure to wean from mechanical ventilation ≤48 hours (p < 0.001), acute renal failure (p = 0.001), and hospital length of stay (LOS). Statistically significant associations were similarly seen when calculated optimal INR values were used. Optimal INR turn point was found to be associated with a significant increased risk of long LOS (optimal INR = 1.03, OR: 1.7, 95% confidence interval [CI]: 1.33–2.18; p < 0.001) and a significant decreased risk of bleeding requiring transfusion (INR = 1.005, OR: 0.732, 95% CI: 0.681–0.786; p < 0.001). High preoperative INR values were independently and significantly associated with an increased risk of multiple postoperative complications. Current guidelines for INR <1.5 should be reassessed for patients undergoing rTKA.
Keywords: international normalized ratio; revision total knee arthroplasty; postoperative; complications; outcomes